Impact of the COVID-19 Pandemic on Breastfeeding Support Services and Women’s Experiences of Breastfeeding: A Review - Lubbe W; Niela-Vilén H; Thomson G; Botha E (Dove Medical Press, 2022)
Welma Lubbe,1 Hannakaisa Niela-Vilén,2 Gill Thomson,3 Elina Botha4 1School of Nursing Science/NuMIQ Research Focus Area, Faculty of Health Sciences, North-West University, Potchefstroom, South Africa; 2University of Turku, Department of Nursing Science, Turku, Finland; 3School of Community Health and Midwifery, University of Central Lancashire, Preston, UK; 4School of Social Services and Health Care, Tampere University of Applied Sciences, Tampere, FinlandCorrespondence: Welma Lubbe, Email welma.lubbe@nwu.ac.zaObjective: The aim of this systematic review was to explore the impact of the COVID-19 pandemic on breastfeeding support services and continuation rates.Methods: Electronic searches were undertaken in seven databases: Academic Search Complete, Springer Nature Journals, CINAHL Medline, Health Source: Nursing/Academic Edition, Masterfile premier, and SocINDEX. Publications following the COVID-19 pandemic between January 2020 and March 2022 were searched for using the following keywords: impact or effect or influence and breastfeeding support and breastfeeding continuation and COVID-19 or coronavirus. Fifteen studies were included for investigation and extracted to identify seven themes related to breastfeeding support during COVID-19.Results: Factors which impacted breastfeeding support during the COVID-19 pandemic included separation, lack of skin-to-skin contact, insufficient support, online breastfeeding support, the impact of the pandemic on breastfeeding rates and experiences, fears of the pandemic, and the need for additional support. The pandemic mostly influenced breastfeeding support negatively, with a small exception occurring where some mothers experienced lockdown as positive since it protected the mother-infant dyad from unwanted visitors. Virtual breastfeeding support was introduced in many contexts; however, practitioners and mothers reported that this could not replace the need for face-to-face support.Conclusion: Breastfeeding is a lifesaving intervention, especially in the face of a disruption such as a pandemic. This work highlights the need for clear, consistent, and evidence-based information about risks, and for key practices to be maintained including not separating mothers and infants, promoting skin-to-skin contact, and ensuring availability of high-quality breastfeeding support.Keywords: breastfeeding support, COVID-19, coronavirus, pandemic, effect